2001
DOI: 10.1007/s002800170003
|View full text |Cite
|
Sign up to set email alerts
|

Oral therapy with proteolytic enzymes decreases excessive TGF-β levels in human blood

Abstract: These results support the concept that OET is beneficial in diseases characterized in part by TGF-beta1 overproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
11

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 0 publications
2
25
0
11
Order By: Relevance
“…Over-production and/or activation of TGFb contribute to persistent inflammation (Chen & Wahl 1999). Papain -in combination with other proteolytic enzymes (trypsin and chymotrypsin) -significantly reduced TGF-b1 levels in patients with rheumatoid arthritis (p50.005), osteomyelofibrosis (p50.05) and herpes zoster (shingles) (p50.05) (Desser et al 2001). It also reduced (p50.001) radiotherapy-associated inflammatory side effects (mucositis and skin reaction) in head and neck cancer patients (Gujral et al 2001).…”
Section: Anti-inflammatory Activities Of Papaya-associated Phytochemimentioning
confidence: 94%
“…Over-production and/or activation of TGFb contribute to persistent inflammation (Chen & Wahl 1999). Papain -in combination with other proteolytic enzymes (trypsin and chymotrypsin) -significantly reduced TGF-b1 levels in patients with rheumatoid arthritis (p50.005), osteomyelofibrosis (p50.05) and herpes zoster (shingles) (p50.05) (Desser et al 2001). It also reduced (p50.001) radiotherapy-associated inflammatory side effects (mucositis and skin reaction) in head and neck cancer patients (Gujral et al 2001).…”
Section: Anti-inflammatory Activities Of Papaya-associated Phytochemimentioning
confidence: 94%
“…Two different studies have demonstrated that two different oral proteolytic enzyme supplements were able to reduce high levels of transforming growth factor-β, which may be a factor in some cancers [172,173]. In the Slovak Republic an oral enzyme supplement was tested in a placebo-controlled trial of multiple myeloma.…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, proteolytic enzymes reduce TGF-β overproduction at the levels of RNA and protein synthesis. 15 It was observed that tumor cells emitted factors blocking the immune system. Thus, tumor cells protect themselves from being recognized by antibodies and from the attack by cells of the immune system by shedding soluble surface antigens.…”
Section: Basis Of Evidence-based Complementary Medicine In Oncologymentioning
confidence: 99%